Homosexuel et hétérosexuel : les termes en question - Jonathan Ned Katz (Glad!)
It is particularly unsettling, I think, to speak of heterosexual history, for that history challenges our usual, implicit, deterministic assumption that heterosexuality is fixed, timeless, biological, synonymous with the conjunction of female and male organs and acts. To the contrary, I argue, heterosexuality (like homosexuality) has an unheralded, various past, and an open, undetermined future. To paraphrase Karl Marx, women and men make their own sexual and affectional history. But they do not make this history just as they please. They make it under circumstances given by the past and altered by their political activity and organization, and their vision of a valued future.